Preventive and Therapeutic Effects of Malaysian Trigona Honey Against Pathogenicity Induced by Staphylococcus aureus Infection in Wistar rats: Biological and Molecular Study - kafaween, Ibrahim Khaled Al-; Hilmi, Abu Bakar Mohd; Soliman, Mohamed M. (International Journal of Psychosocial Rehabilitation, 2020)
The increase of drug-resistant bacteria against the existing antibiotics inspire investigators to look for various natural remedies and investigated their potential based on scientific value. Malaysian Trigona honey (MTH) has a therapeutic application for the wounds and chronic infections. Study of bacterial infection with an animal model following stingless bee honey ingestion is less and needs further investigation. Therefore, we aim to investigate the effectiveness of MTH in Wistar rats infected by Staphylococcus aureus infection at cellular, molecular study. Materials and methods: Twenty five Wistar rats divided into five groups according to different experiments, negative control group was fed with water, positive control group was fed MTH orally (5 g/kg body weight), untreated group was infected by S. aureus without MTH feeding, therapeutic group was infected by S. aureus followed by treatment with MTH and preventive group was administrated MTH one week before S. aureus infection. Blood from orbital sinus was obtained after 3 weeks of MTH feeding for biochemical analysis. Lung tissues were collected for molecular analysis and total bacterial count. Results: Total colony forming unit (CFU) of lung showed significantly decreased (P < 0.05) in preventive and therapy groups compared with untreated group. Serum levels of GPx, SOD, and CAT in positive control group were significantly increased compared with negative control group, and in the untreated group were decreased (P< 0.05). While in the preventive and therapy groups serum levels were increased (P< 0.05) compare with untreated group. Compared to the negative control group mRNA expressions of SOD, GST, and GPx in the positive control group were significantly upregulated (P